Modalities in Khofiah Indah Parawansa's Victory in the 2018 East Java Governor Election - Zahro, Maharina Novia; Sujoko, Anang (Universitas Muhammadiyah Malang, 2023)
The dominance of the Muslim community in East Java and the existence of a patriarchal culture affect voter behavior, making it difficult for women to become governors. This study aims to reveal the success factors of women, namely Khofifah Indah Parawansa, to become Governor in East Java from the aspect of his modalities based on Piere Boerdiau's perspective. This research uses a type of qualitative research with narrative analysis. This research shows that Khofiah's victory is inseparable from the ability to maximize all types of modalities owned, namely social capital, cultural capital, and symbolic capital. All types of modalities were then packaged very well by the political public relations of Khofifah's winning team so as to win a lot of public sympathies and greatly contribute to Khofiah's victory.